RELIABILITY ANALYSIS OF BENDING, SHEAR AND DEFLECTION CRITERIA OF REINFORCED CONCRETE SLABS (Nigerian Journal of Technology, 2014)
Reliability analysis of the safety levels of the criteria for bending, shear and deflection of singly reinforced, concrete slabs, have been evaluated over the practical range of thicknesses 100mm to 250mm.  The First Order Reliability Method was employed in the evaluation procedure for continuous slabs of equal spans as a case study.  Results indicate that the safety margins proposed and associated with the probability of failure (given as 1 x 10-6) for singly reinforced concrete slabs, in the British [CP110; BS8110] and European [EC2] codes for design are not achieved at all.  Also, the reliability levels are not uniform.  Thus, the current design formulations are not as safe and reliable as predicted.  This is because the intrinsic probability of failure, in bending, for example, is only 0.022, which, corresponds to an implied safety level of 2.015. Therefore, the design formulations in these codes need a review so that they can at least meet the target for approved structural safety as prescribed by the Joint Committee on Structural Safety.